2013
DOI: 10.1177/0268355513495830
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical ablation in patients with chronic venous disease: A prospective multicenter report

Abstract: MOCA of the saphenous veins has the advantage of endovenous ablation without tumescent anesthesia, making it an almost pain-free procedure. High occlusion rates with significant clinical improvement can be achieved with this method at short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 10 publications
1
33
0
2
Order By: Relevance
“…Bishawi et al indicate that this procedure has a very high effectiveness, reaching 97% in the first 6 weeks after the procedure. Effectiveness is maintained at the level of 96% over 2 years of follow-up [13]. Elias estimated the effectiveness at 96.7% in a follow-up lasting 260 days [14].…”
Section: Discussionmentioning
confidence: 96%
“…Bishawi et al indicate that this procedure has a very high effectiveness, reaching 97% in the first 6 weeks after the procedure. Effectiveness is maintained at the level of 96% over 2 years of follow-up [13]. Elias estimated the effectiveness at 96.7% in a follow-up lasting 260 days [14].…”
Section: Discussionmentioning
confidence: 96%
“…showed anatomical success rates of 88% after RFA [10]. Our recent study on MOCA™ in SSV showed an occlusion rate of 97% in the group treated according to our current study protocol [17]. A Chi-square test with a one-sided 0.05 significance has a power of 80% to observe no difference between both groups, when each group consists of 74 patients (non-inferiority principle, range 2%).…”
Section: Method/designmentioning
confidence: 88%
“…Patients were satisfied after treatment [14]. Several other studies reported promising data on feasibility, safety, anatomical and clinical success regarding MOCA treatment in GSV insufficiency, without major complications [1517]. …”
Section: Introductionmentioning
confidence: 99%
“…One-month to six-month occlusion rates of >90% were documented in other series. [15,16] When compared to RFA, it was reported that MOCA caused lesser postoperative pain and discomfort. [17] To document the non-inferiority of MOCA compared to RFA, Mechanochemical Endovenous Ablation versus RADiOfrequeNcy Ablation (MARADONA) Trial for GSV and Mechanochemical Endovenous Ablation versus Radiofrequency Ablation (MESSI) Trial for lesser saphenous vein (LSV) are still ongoing.…”
Section: Mechanochemical Ablationmentioning
confidence: 99%